2018
DOI: 10.1186/s13104-018-3190-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor volume reduction of nasal carcinomas versus sarcomas in dogs treated with definitive fractionated megavoltage radiation: 15 cases (2010–2016)

Abstract: ObjectiveLocal control is a major challenge in treating canine nasal tumors, and cytoreduction following radiation therapy has been recommended to extend survival and to delay local recurrence. Our objective was to compare the effect of definitive radiotherapy on the tumor volume of intranasal carcinomas compared to sarcomas. We evaluated 15 dogs that received radiotherapy within 1 month of initial CT scan, and post radiation CT scans performed within 3 months of completing full course definitive megavoltage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
2
24
1
Order By: Relevance
“…A recent study demonstrated complementary results regarding tumor type, wherein carcinomas had a greater volume reduction than sarcomas following fractionated megavoltage radiation. 54 This supports the premise that tumors that rapidly respond to radiation therapy often also have rapid recurrence and growth, which is reflected in the difference in progression-free interval between sarcomas and carcinomas demonstrated here. However, it is possible that this apparent difference reflects a selection bias, such as if the dogs with sarcomas were cases deemed more amenable to radiation therapy than others, or if other dogs with sarcomas were excluded from the study because they died or were euthanized before the initial 6-week follow-up period.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study demonstrated complementary results regarding tumor type, wherein carcinomas had a greater volume reduction than sarcomas following fractionated megavoltage radiation. 54 This supports the premise that tumors that rapidly respond to radiation therapy often also have rapid recurrence and growth, which is reflected in the difference in progression-free interval between sarcomas and carcinomas demonstrated here. However, it is possible that this apparent difference reflects a selection bias, such as if the dogs with sarcomas were cases deemed more amenable to radiation therapy than others, or if other dogs with sarcomas were excluded from the study because they died or were euthanized before the initial 6-week follow-up period.…”
Section: Discussionsupporting
confidence: 89%
“…19,75,95,96,116 These doubling times would correspond to latency periods of 1 to 3 years based on the calculation presented above. However, these estimates are likely conservative since cancer is not typically diagnosed as soon as it reaches the threshold of clinical detection; in dogs, cancers are often diagnosed, or present for treatment, in the range of 2.5 to 10 cm 49,62,63,74,78,83,98,105,107,108,117 (containing 10 billion to 500 billion cells), corresponding to latency periods upwards of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…19,75,95,96,116 These doubling times would correspond to latency periods of 1 to 3 years based on the calculation presented above. However, these estimates are likely conservative since cancer is not typically diagnosed as soon as it reaches the threshold of clinical detection; in dogs, cancers are often diagnosed, or present for treatment, in the range of 2.5 to 10 cm 49,62,63,74,78,83,98,105,107,108,117 (containing 10 billion to 500 billion cells), corresponding to latency periods upwards of 5 years. This estimate is consistent with multi-year latency periods previously documented in dogs following exposure to ionizing radiation: 2 to 10+ years for bone malignancies, 43,59,76 2 to 4 years for hemangiosarcomas, 116 4 to 10+ years for hepatic malignancies, 48 and 3 to 10+ years for pulmonary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The grouping was as follows: A: control group, intraperitoneal injection of normal saline every 12 h; B: cisplatin group, intraperitoneal injection of cisplatin (0.1 g/mL) followed by injection of normal saline 12 h later; C: quercetin group, Intraperitoneal injection of quercetin (2.5 g/mL) followed by injection of normal saline 12 h later; D: Cisplatin → metformin group, intraperitoneal injection of cisplatin (0.1 g/mL) followed by metformin (1.5 g/mL) 12 h; E: quercetin + cisplatin + metformin group, intraperitoneal injection of a mixture of quercetin (2.5 g/mL), cisplatin (0.1 g/mL) and metformin (1.5 g/mL), injection of normal saline 12 h. Each group was administered once a day, 100 μL/nude mouse, for 5–8 days. During the experiment, the maximum diameter (LD) and minimum diameter (SD) of the tumor were measured every 3 days, and the calculation formula 19 of tumor volume (V) = LD × SD 2 × 0.52, tumor growth rate, and tumor growth inhibition rate (TGI) were calculated. Compare and analyze the difference of single-drug, two-drug combination and three-drug combination.…”
Section: Methodsmentioning
confidence: 99%